Multiplex PCR Pathogen Detection in Acute Gastroenteritis Among Hospitalized US Children Compared With Healthy Controls During 2011–2016 in the Post–Rotavirus Vaccine Era - Harrison, Christopher J; Hassan, Ferdaus; Lee, Brian; Boom, Julie; Sahni, Leila C; Johnson, Coreen; Dunn, James; Payne, Daniel C; Wikswo, Mary E; Parashar, Umesh; Selvarangan, Rangaraj (Open forum infectious diseases, 2021)
Abstract Background Despite vaccine-induced decreases in US rotavirus (RV) disease, acute gastroenteritis (AGE) remains relatively common. We evaluated AGE pathogen distribution in hospitalized US children in the post–RV vaccine era. Methods From December 2011 to June 2016, the New Vaccine Surveillance Network (NVSN) conducted prospective, active, population-based surveillance in hospitalized children with AGE. We tested stools from 2 NVSN sites (Kansas City, Houston) with Luminex x-TAG Gastrointestinal Pathogen Panels (Luminex GPP) and analyzed selected signs and symptoms. Results For 660 pediatric AGE inpatients and 624 age-matched healthy controls (HCs), overall organism detection was 51.2% and 20.6%, respectively (P < .001). Among AGE subjects, GPP polymerase chain reaction detected >1 virus in 39% and >1 bacterium in 14% of specimens. Detection frequencies for AGE subjects vs HCs were norovirus (NoV) 18.5% vs 6.6%, RV 16.1% vs 9.8%, adenovirus 7.7% vs 1.4%, Shigella 4.8% vs 1.0%, Salmonella 3.1% vs 0.1%, and Clostridioides difficile in ≥2-year-olds 4.4% vs 2.4%. More co-detections occurred among AGE patients (37/660, 5.6%) than HCs (14/624, 2.2%; P = .0024). Per logistic regression analysis, ill contacts increased risk for NoV, RV, and Shigella (P < .001). More vomiting episodes occurred with NoV and RV, and more diarrheal episodes with Shigella and Salmonella. Modified Vesikari scores were highest for Shigella and lowest for C. difficile. Conclusions NoV detection was most frequent; however, RV remained important in hospitalized AGE in the post–RV vaccine era. Continued active surveillance is important to document ongoing vaccine effects, pathogen emergence, and baseline disease burden for new vaccines.